Behaviour of square concrete-filled stiffened steel tubular stub columns under axial compression. Issue 8 (June 2019) - Yuan, Fang; Huang, Hong; Chen, Mengcheng
As China's infrastructure grows rapidly, the use of concrete-filled steel tubular structures for engineering applications is attracting increasing interest owing to their high section modulus, high strength and good seismic performance. However, for concrete-filled steel tubular members with large width-to-thickness ratio, steel tubes are prone to outward buckling when they are subjected to axial compression. Welding of longitudinal stiffeners on the steel tubes is one of the most efficient approaches for delaying local buckling and thus improving the mechanical performance of such type of concrete-filled steel tubular members. This study attempts to investigate the axial compression behaviour of concrete-filled stiffened steel tubular members with square sections through experimental study and finite element analysis. First, 14 concrete-filled steel tubular stub columns, with different width-to-thickness ratios of steel tube and depth-to-thickness ratios of stiffener, were subjected to axial compression loads and tested. It was found that the use of stiffeners increases the ultimate strength and improves the stability of the stub columns. Later, an investigation on the behaviour of the stiffened concrete-filled steel tubular stub columns was carried out through a three-dimensional finite element analysis. The accuracy of the finite element analysis model was verified by the test results. A parametric study was conducted to further evaluate the stiffening schemes that influence the axial compression strength. Finally, the research findings were synthesized into a new simplified model to predict the load-carrying capacity of stiffened concrete-filled steel tubular stub columns that allows for large width-to-thickness ratios.